Silver Nanoparticle-Based Finishing for Leather Antimicrobial and UV Protection - Claudia Cirillo; Mariagrazia Iuliano; Francesca Fierro; Claudia Florio; Gaetano Maffei; Andrea Loi; Todor Batakliev; Maria Sarno (Micromachines)
This study focuses on preparing and characterizing functionalized silver nanoparticle-based (Ag-F NPs) finishing agents for leather treatment. Ag-F NPs were synthesized and functionalized through a ligand exchange process with citric acid, enhancing their dispersion stability in aqueous media. The nanoparticles were incorporated into polyurethane- and nitroemulsion-based finishing formulations and applied to ovine and bovine leather via a spray coating process. Morphological (SEM, TEM), structural (XRD), thermal (TGA), and spectroscopic (FT-IR) analyses confirmed successful functionalization and uniform dispersion within the finishing layer. Leather samples treated with Ag-F NPs exhibited a significant improvement in antibacterial properties, with microbial growth reduction of up to 90% after 72 h. Additionally, accelerated aging tests demonstrated enhanced UV resistance, with a 30% lower color change (∆E) compared to control samples. The Ag-F NPs-based finishing layers also exhibited superior abrasion and micro-scratch resistance, maintaining a stable coefficient of friction over time. These findings demonstrate the potential of Ag-F NPs as multifunctional leather-finishing agents, making them highly suitable for applications in the automotive, footwear, and leather goods industries.